A New and Rather Long Proof of the Pythagorean Theorem by Way of a Proposition on Isosceles Triangles. (1st November 2016) - Basu, Kaushik
Summary: This paper provides a new, long proof of the Pythagorean theorem. The two lemmas used should be of some intrinsic interest, especially one on isosceles triangles.